Peter Faber, inspirator and forger of the first Society of Jesus - García de Castro, SJ, José (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
One of the first seven Jesuits gathered in Paris (1528-1536), Peter Faber carried out a very important role in the foundation and consolidation of the Society of Jesus, which remains to be discovered and appreciated. A first companion of Ignatius of Loyola at Saint Barbara College, first in making the full Thirty Day Retreat with him, Faber enjoyed great esteem and «authority» among the First Companions, and was recognised by all of them as the «older brother» of the group. This article focuses on four different dimensions of this young Saboyan Jesuit`s personality in an attempt to give reason to Faber`s primacy in the group: he was simple and had a profound anthropological configuration, of a competent intellectual and theological formation, with extraordinary gifts for spiritual conversation and a particular way of offering and living the Spiritual Exercises, a ministry in which he «got the first place», according to Ignatius. The approach and delving into the life and worth of Peter Faber in the «Group of Paris» and in the first Society of Jesus is necessary to understand the spirituality and charisma of this new group that grew so powerfully in one of the most «convulsive» centuries in the history of the Church.